Cochlear implantation in a patient with large vestibular aqueduct syndrome: A case report - (:unkn) unknown (My University, 2004)
Large vestibular aqueduct syndrome (LVAS) is a distinct clinical entity characterized by fluctuative sensorineural hearing loss associated with isolated enlargement of the vestibular aqueduct. In this report, we present our experience with cochlear implantation in a patient with LVAS.
Keywords: Coclear implant; Enlarged vestibular aqueduct; Hearing loss; Large vestibular aqueduct syndrome